Who Is the King of Glory? Identifying and Explaining Two Examples of Patristic Prosopological Exegesis with a Brief Critique of Matthew Bates - Willis, Timothy Scott (Journal of theological interpretation, 2024)
This article explores two proposed instances of patristic prosopological exegesis in Ps 24: the identification of the King of glory with the resurrected and ascending Jesus, and the antiphonal speakers of vv. 7-10 with angelic guards at the gates of heaven. Far from being arbitrary connections, notable textual ambiguities and typological elements accessible to ancient authors ground the identifications in the psalm text. These examples of patristic exegesis fit generally within the research of Matthew Bates, but they provide a basis for slightly modifying his proposed definition of prosopological exegesis.